IgA Vasculitis involving four systems - Joana Diogo; Carolina Coelho; Rita Monteiro; Ângela Ghiletchi (Galicia Clínica, 2022)
Henoch-Schonlein Purpura (HSP) is a systemic vasculitis that infrequently occurs in adults. While rheumatological and gastrointestinal complications are common, lung involvement is a rare complication. We report the case of a 70 year-old female that presented to the hospital with purpuric lesions on her legs. During her hospital stay she developed respiratory distress, and the computed tomography (CT) scan showed evidence of Diffuse Alveolar Hemorrhage (DAH). She also had renal dysfunction, and the renal biopsy confirmed the presence of leukocytoclastic vasculitis on histology, consistent with HSP. The patient was initiated on steroids, in addition to supportive management, leading to the resolution of her symptoms. This case is unique, as it presents a rare complication of HSP, with pulmonary disease, causing DAH. Furthermore, adult onset HSP is also an uncommon occurrence. It is very important to recognize DAH early in HSP, as it holds a high mortality rate.